PERAN MANAJER DALAM IMPLEMENTASI FUNGSI MANAJEMEN DI UNIT REKAM MEDIS DAN INFORMASI KESEHATAN RSU PKU MUHAMMADIYAH PRAMBANAN - Rezyana Budi Syahputri; Rheni Haryanti; Sri Handayani (Universitas Muhammadiyah Klaten, 2024)
Management functions consisting of planning, organizing, implementing, and supervising that runs properly and correctly is one characteristic of a well-functioning organization. Hospitals are healthcare institutions that provide medical services and support services to patients. Good support services in the Medical Records and Health Information (MRHI) unit at the hospital require good management to manage the unit. The MRHI unit has the responsibility of creating and maintaining patient medical records. The purpose of this study is to determine the role of the head of the medical support sub-sector as a manager in implementing the management functions of the MRHI unit at PKU Muhammadiyah Prambanan Hospital. This research is a qualitative study with a descriptive method. The results show that the manager's role is quite good in implementing management functions. This is evidenced by the well-organized planning process by the head of the medical support sub-sector so that activities can run continuously. In terms of organization, it is still quite minimalistic but already structured because the hospital has only been established for 2 years and patient visits are still not too many. In the implementation function, the manager is able to provide good guidance to the staff, although at this stage, the staff has not fully performed their duties according to procedures. The supervision function runs very well, indicated by the service provided being directed, orderly, and in accordance with established rules. The implementation of management functions can be maintained by improving the management functions that are not yet optimal.